Research Anthology on Remote Teaching and Learning and the Future of Online Education 2022
DOI: 10.4018/978-1-6684-7540-9.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Online Teaching and Learning in Higher Education Settings

Abstract: This chapter intends to answer the question, “What are some guidelines for working effectively in virtual teams?” To further advance existing literature, the authors utilized a qualitative phenomenological approach with a randomly-sampled group of seven students who had completed master's-level education courses that were conducted in an online format at a private Midwestern University. Students were halfway through their course completion at the time of data collection. In addition, a random sample of one pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This showed that the internet serves different purposes for distant learners, hence why any disruption in its accessibility is a significant issue for the learners. This agrees with the submission of [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This showed that the internet serves different purposes for distant learners, hence why any disruption in its accessibility is a significant issue for the learners. This agrees with the submission of [15].…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, [15] notes that technology plays a crucial role in online education and continues to do so in ODL among students due to its flexibility. Following the same line of thought, ODL educators found that the use of technology can enhance interaction and collaboration among learners and aid in handling many learners from different parts of the world, which makes its adoption a cheap teaching method [16].…”
Section: Internet Accessibility and Open And Distancementioning
confidence: 99%
“…The managerial and social aspects of online learning and teaching are critical for the success of online students ( Baran and Jones, 2020 ). Effective planning, learner preparation, and enhanced interaction have to be ensured by designers of online teaching and learning platforms and programs ( Rapanta et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online courses are specifically designed for asynchronous learning. In this case, the educational material is delivered to students at different times considering that different students have different schedules in mind [Barker, 2020]. For example, some students may work a little bit each evening, while others will devote weekend stretches to their studies.…”
Section: Online Teaching Vs Emergency Remote Teachingmentioning
confidence: 99%
“…As far as the educational material is concerned, in an online course, the material is created in such a way that a systematic and well-organized path is formed to introduce them to the learning process [Barker, 2020]. The provided material could comprise of online simulations, embedded quizzes, online lab exercises, forum discussions and they are all set up ahead of time and placed at key checkpoints to enhance the understanding of the curriculum.…”
Section: Online Teaching Vs Emergency Remote Teachingmentioning
confidence: 99%